Evaluation of transient temperature rise of MY1016 DC motor in standard cycle - Muhammad Syawal, Mat Jahak; Mohd Azri Hizami, Rasid; Sutiman, . (AIP Publishing, 2024)
The MY1016 DC motor is a popular choice among hobbyist for electrification of bicycle and scooter. With frequent acceleration and deceleration, the fluctuating current drawn from the power supply increases the motor temperature. In this study, we develop a temperature-integrated motor controller that allows us to control the speed profile of the motor and evaluate several motor components’ temperature when it is operated in several standard electric motorcycles, IEC. It was shown that the highest temperature inside the motor is the brush, followed by the bearing and the permanent magnet. SI which is the steady state IEC cycles generates the highest temperature on the brush at 81°C, while S5 which is an intermittent periodic with electric braking cycle generates the lowest temperature at 45°C. Any abrupt acceleration with a duration less than 10 seconds has no consequence on the temperature of the machine.